Evaluation of optic nerve head and macula parameters pre-and post external beam radiotherapy in patient with head and neck tumor - Keong, Tan Chai (2018)
Head and neck cancers is one of the tenth most common cancer worldwide with high mortality and morbidity rate. Due to its location, surgical clearance is often difficult and require radiotherapy and chemotherapy to achieve locoregional control. Therefore, radiotherapy is considered the mainstay treatment in head and neck cancers. Despite advancement of laser beam, radiation protocol and protective equipment, radiation damage to surrounding normal tissue is inevitable. Radiation optic neuropathy and retinopathy are known ocular complication following radiotherapy. Early detection and prompt early treatment might prevent debilitating visual loss. Optical coherence tomography of macula and optic nerve head parameters will be able to provide an objective measurement and evaluation of above areas. Objectives: Our objective of this study is to compare mean macular thickness and optic nerve head parameters pre-and six-month post external beam radiotherapy in patient with head and neck tumours. Methods: A cross sectional study involving 30 patients histologically diagnosed head and neck cancers. Patient who fulfilled inclusion and exclusion criteria were recruited from a single centre in Malaysia. Recruitment was carried out between December 2016 and August 2017. Evaluation of optic nerve head parameters and macular thickness were conducted using Spectral Domain-Cirrus optical coherence tomography. Optic nerve head parameters, retinal nerve fibre layer (RNFL) thickness and macular thickness were evaluated prior to radiotherapy. A repeat procedure was conducted six months post external beam irradiation. Assuming both eye received similar radiation exposure, right eye ONH parameters and macular thickness are analysed and discussed in this study. Descriptive analysis, paired t-test and multivariate ANCOVA method is performed in this study using SPSS. Result: Macular is thinner in post radiotherapy, but without statistically significant. There were no changes in mean optic nerve head parameters between pre-and post radiotherapy period. Mean RNFL thickness showed thickening in the post radiotherapy period. Temporal and inferior quadrant of RNFL showed thickening in post radiotherapy period, in which inferior quadrant showed statistically significant result. Conclusion: There was thinning of macular thickness and thickening of optic nerve head RNFL in six-month post radiotherapy. But the changes were small and it is too early to justify the parameters. Further researches, larger studies and longer follow up period need to be conducted before we can further draw the conclusion of other parameters related to early exposure to radiation.